1995
DOI: 10.1002/art.1780381111
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of leflunomide in the treatment of patients with active rheumatoid arthritis

Abstract: Objective. To assess the safety and effectiveness of leflunomide versus placebo in patients with active rheumatoid arthritis (RA) treated for 6 months.Methods. Four hundred two patients were randomly assigned to receive placebo or leflunomide at 5 mg, 10 mg, or 25 mg daily. A washout period of 6-12 weeks from prior second-line therapy was required.Results. Statistically significant improvement in primary and secondary outcome measures, as well as by responder analyses, occurred in the 10-mg and 25-mg dosage gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0
9

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 269 publications
(169 citation statements)
references
References 27 publications
4
156
0
9
Order By: Relevance
“…Efficacy ranging from 50 to 87% with monotherapy using various assessment criteria, have been observed in studies in different situations to date, irrespective of the absence of the loading dose. [5][6][7][11][12][13][14][15][16][17] Hematological and biochemical parameters showed no significant change. Few patients had liver enzyme elevation, though it did not reach significance and only one had to discontinue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficacy ranging from 50 to 87% with monotherapy using various assessment criteria, have been observed in studies in different situations to date, irrespective of the absence of the loading dose. [5][6][7][11][12][13][14][15][16][17] Hematological and biochemical parameters showed no significant change. Few patients had liver enzyme elevation, though it did not reach significance and only one had to discontinue.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown liver enzyme elevation, which subsequently normalized. [6,7,[15][16][17] Twenty four (29%) patients dropped out of the study and an adverse event was observed in 15 patients, of which five withdrew. Skin reactions observed were more of type B adverse event, which were unpredictable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized controlled clinical trials have established leflunomide as an alternative to MTX as monotherapy, especially for patients who cannot tolerate MTX or are experiencing an inadequate response to MTX (62,63,75,(86)(87)(88)(89). The reduction in RA disease activity and in the rate of radiologic progression achieved by leflunomide appears to be equivalent to that of a modest dosage of MTX.…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%
“…In a phase II study (154), 402 patients with active RA were enrolled in a 6-month, multicenter, double-blind comparison of three dose levels of leflunomide (5, 10, or 25 mg) with placebo. Statistically significant improvement in primary and secondary outcome measures occurred in the 10-and 25-mg groups compared to placebo.…”
Section: Leflunomidementioning
confidence: 99%